Effect of giving premix cookies with mung beans and anchovy (Stolephorus) for stunting prevention on toddlers in Telaga Sari Village, Tanjung Morawa District, Deli Serdang Regency - Pulungan, Fitriyani; Batubara, Ardiana; Nasution, Erlina (Journal of Health Science and Medical Therapy, 2024)
Stunting is when a child's body length or height is less than their age. Several factors cause stunting, including energy and nutritional intake, and babies born with low birth weight (LBW). Apart from being found in milk, sources of protein and calcium can also be found in various other foods, both animal and vegetable. One source of protein and calcium is green beans and anchovies. This research was conducted in Telaga Sari Village, Tanjung Morawa District, Deli Serdang Regency. This research aims to determine how giving premix cookies mung bean and anchovy prevents toddler stunting. This type of research is quasi-experimental with a pretest–post-test research design. The sample in this study was 60 toddlers, with 30 intervention groups and 30 control groups. Where before and after the treatment, body height was measured. Analysis was carried out in the research using the t-test with a confidence level of 95%. The results of the study showed that the mean TB/U before giving premix cookies mung bean and anchovy in the intervention group was -0.99 ± 2.332, and after giving the results showed it was -0.02 ± 1.562, while the control group had a TB / U of -0 .05±1.785. Conclusion: The results of the dependent t-test obtained p=0.001 (p≤0.05), which means that there is a significant effect before and after giving premix cookies mung bean and anchovy on the prevention of stunting in toddlers with a difference in the average TB/U of toddlers of -0.97.